Potential hazard of open space fire in black pine stands (Pinus nigra J.F. Arnold) in regard to fire severity - Barčić, Damir; Dubravac, Tomislav; Vučetić, Marko, meteorolog (2020)
Black pine (Pinus nigra J.F. Arnold) is one of the most important reforestation species for dry and rocky terrain in the sub-Mediterranean zone. Fire is an important factor in black pine stands that largely defines the distribution range of black pine and the floristic composition of its stands. Fire causes less damage during autumn or early spring when tree cones contain ripe seeds that can partially reforest burnt surfaces. Every fire is a potentially significant threat to forest habitats. There are many damages, from direct damages to wood mass and reforestation costs, to indirect ecological, edaphic, protective damages and the loss of biological diversity. The aim of prevention works in forestry is to reduce the number of fires and reduce burnt surface area per fire. Research was based on vegetation analysis performed on each experimental plot in a black pine stand. The assessment of fire severity was performed using the Canadian Forest Fire Weather Index (FWI). The assessment of the severity of fire indicates the suitability of conditions for the occurrence of forest fires, and enables sound and effective protective methods beginning with silvicultural works. The results indicate better quality stands in the higher parts of the sub-Mediterranean area. Taking into account the climatic parameter, the areas on the border with the continental climate have better habitat conditions for black pine. Also, attention should be focused on 2012 and 2015. High values (Figure 13 – 16.22, Figure 11 – 6.99, Figure 8 – 8.38, Figure 7 – 12.02 and 12.25, Figure 5 – 8.32) indicate the overlapping of extremely dry periods and extremely high summer temperatures, and probably a strong wind influence that further increases the index. Fire severity assessments indicate the suitability of conditions for the onset of fire.
Bibliografija: str. 7-8.
Summary.
Keywords: Crni bor -- Pinus nigra J. F. Arnold -- Šumski požari -- Zapaljivost; Submediteran